Enhancing resilience in single-parent family adolescents in China: a randomized controlled trial based on home-school collaborative intervention - Binrong Dai; Yujie He; Mei Peng (BMC Public Health)
Abstract Background It remains unknown whether home-school collaborative strategies can improve the resilience of adolescents and children from single-parent families in China. Objectives This study addresses the gap in resilience interventions for single-parent family students by validating a 7-week home-school collaborative intervention strategy. Methods The participants were 89 primary and secondary school children from China, randomly assigned to either the experimental group (20 single-parent and 27 non-single-parent students) or the control group (20 single-parent and 22 non-single-parent students). Both groups used the Adolescent Psychological Resilience Scale to report their resilience levels during the pre-test and post-test phases. Single-parent family parents also reported their collaborative participation using a behavior checklist. Results The experimental group exhibited higher resilience gain scores compared to the control group. The intervention effects in the experimental group remained stable for one month after the intervention ended. Additionally, the intervention at the school level fostered greater collaborative involvement from single-parent families, particularly in terms of family support participation. Conclusions The Home-school collaborative intervention strategy is a valuable measure for enhancing the resilience of students from single-parent families and has the potential for application within both family and school contexts.